Panurgus platymerus Pérez, 1895 (Hymenoptera: Andrenidae) synonymy, status of the Warncke lectotype - Patiny, Sebastien (Zootaxa, 2003)
The usual definition of Panurgus platymerus Pérez, 1895 does not fit the lectotype designated by Warncke in the Pérez collection. We propose here to place the specimens previously determined as Panurgus platymerus under the name Panurgus pyropygus Friese, 1901. Panurgus platymerus will be reserved for specimens of a large North-African species close to Panurgus cephalotes Latreille, 1811.